Characteristics of Students’ Work as a Result of Calligraphy Art Education at Lemka Sukabumi - Alhail, Hadi; Sugiarto, Eko; Syakir (Gorga : Jurnal Seni Rupa, 2025)
This research examines the characteristics of students' calligraphy artwork at the LEMKA Arabic Calligraphy Islamic Boarding School, Sukabumi, as a result of applied art education. The gap phenomenon found is that there are differences in approaches to calligraphy art education, where some teachers adhere to traditional rules, while others open up space for exploration of contemporary styles. This causes variations in the characteristics of students' work, which have not been widely investigated in previous studies. This research fills the research gap by specifically examining how the curriculum at the LEMKA Islamic Boarding School is reflected in the students' work. Previous studies focused more on aspects of learning management and Islamic boarding school existence strategies, without exploring the relationship between education and the aesthetic characteristics of students' work. The research method used is a qualitative approach with descriptive methods. Data was collected through observation, in-depth interviews, and documentation of the students' works. The analysis technique is carried out through data reduction, data presentation, and drawing conclusions based on aesthetic patterns and Islamic values. The research results show that the work of students at the LEMKA Islamic Boarding School can be classified into four main categories: manuscript calligraphy, manuscript decoration, decoration, and contemporary. Each category reflects the integration of Islamic aesthetics and freedom of expression with variations in the use of khat, colors and decorative elements. This research proves that the characteristics of LEMKA students' calligraphy artwork are based on 2 inseparable aesthetic concepts, namely essential aesthetics and material aesthetics.